Qurara region between stability and transformation, a socioanthropological study of the Timimoun region - Bachir TALHA (Social Sciences Journal, 1970)
This paperis a part of a long-termfieldstudy and a phase of investigation that have notyetended, aims to detect the heritage of Gourara district thatisconsidered to be a richheritagein its dimensions and signs. It isdifficult to know and explore itthrough an individual effort,but itneeds a generation of social scientists in all its branches and specialities to explore theremains of thisheritagewhichstarted to fade because of the changes whichoccured andstillaccuring to affect thisregionyearafteryear.That’swhyweproposed the two-fold (stability and change) as the regioniswitnessingdeeptransformations in the form and content. And alsoit made us investigating the heritage anditssigns in the light of successive changes that have taken place in our first visit (2009) andthe second visit (2016), through the followingpresentationevenitdoesn’t have a detailform dueto the conditions that the scientific articles shouldrequire.